A critical review of 20 years of parotid gland surgery. (2nd July 2016) - Knopf, Andreas; Szyper, Michael; Mansour, Naglaa; Sonnenberg, Jan; Hofauer, Benedikt; Niedermeyer, Hans
Abstract: Conclusion PG surgery provides sufficient radicality with a minimum of functional loss. Patient's outcome is associated with the reliable estimation of the lesional entity/dignity. Diagnostic approaches are required to determine morphological aspects, avoid unnecessary surgery, and to reliable identify primary carcinomas/occult metastases.Objectives The pre-operative assessment of parotid gland (PG) lesions is of major clinical impact, whilst surgery remains the diagnostic/therapeutic mainstay. There are still controversies about the distribution of entities, clinical course, functional outcome, and survival.Methods In total, 1211 patients were retrospectively analyzed for disease-related data. Differences were analyzed using the Chi-square/Fisher exact/unpaired student's t -test; survival by Kaplan-Meier.Results There were 946 benign and 265 malignant tumours. In primary PG malignancy the disease-free/overall survival was 78/127 months. Metastases into the PG demonstrated a decreased survival (67 months). Extended surgery was associated with post-operative facial nerve alteration. Extracapsular dissection and superficial parotidectomy did not show differences in the facial palsy rate.